2018
DOI: 10.1371/journal.pone.0200432
|View full text |Cite
|
Sign up to set email alerts
|

RAMP1 in Kupffer cells is a critical regulator in immune-mediated hepatitis

Abstract: The significance of the relationship between the nervous and immune systems with respect to disease course is increasingly apparent. Immune cells in the liver and spleen are responsible for the development of acute liver injury, yet the regulatory mechanisms of the interactions remain elusive. Calcitonin gene-related peptide (CGRP), which is released from the sensory nervous system, regulates innate immune activation via receptor activity-modifying protein 1 (RAMP1), a subunit of the CGRP receptor. Here, we sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…RAMP1 signalling in immune cells attenuates inflammation in the skin and lung 30 . We also showed that CGRP interacts with immune cells to regulate inflammatory cytokines, which results in reducing chemical‐induced inflammation in the intestine 19 and liver 20 . In addition to its role in regulating inflammation, we showed that CGRP/RAMP1 signalling interacts with macrophages and fibroblasts to enhance angiogenic responses in mice with skin wounds, 24 peritonitis 26 and, as demonstrated in the present study, endometriosis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…RAMP1 signalling in immune cells attenuates inflammation in the skin and lung 30 . We also showed that CGRP interacts with immune cells to regulate inflammatory cytokines, which results in reducing chemical‐induced inflammation in the intestine 19 and liver 20 . In addition to its role in regulating inflammation, we showed that CGRP/RAMP1 signalling interacts with macrophages and fibroblasts to enhance angiogenic responses in mice with skin wounds, 24 peritonitis 26 and, as demonstrated in the present study, endometriosis.…”
Section: Discussionsupporting
confidence: 83%
“…30 We also showed that CGRP interacts with immune cells to regulate inflammatory cytokines, which results in reducing chemical-induced inflammation in the intestine 19 and liver. 20 In addition to its role in regulating inflammation, we showed that CGRP/RAMP1 signalling interacts with macrophages and fibroblasts to enhance angiogenic responses in mice with skin wounds, 24 peritonitis 26 and, as demonstrated in the present study, endometriosis. Accumulated fibroblasts in endometrial tissue implants appear to promote angiogenesis by inducing VEGF-A, 15,31 although in the present study cultured fibroblasts failed to up-regulate VEGF-A in response to CGRP, which is consistent with our previous findings.…”
Section: F I G U R Esupporting
confidence: 72%
See 2 more Smart Citations
“…An effective method of isolating Kupffer cells was explored to eliminate endothelial cell contamination, which could be meaningful for illuminating Kupffer cell function and mechanism in diseases[22]. RAMP 1 in Kupffer cells mediates a crosstalk network involving infiltration of immune cells and pro-inflammatory cytokines secreted by Kupffer cells and splenic T cells, and such crosstalk network can regulate the immune response[23]. ATG5-dependent autophagy involved in crosstalk between Kupffer cells and cytokines (IL-6 and IL-10) mediated acute liver injury response[24].…”
Section: Cells Involved In Liver Fibrosismentioning
confidence: 99%